Increasing Economic of Santri Nurul Anwar through making Paper Bag at Tejosari Metro City - Suryawahyuni Latief; Bambang Ariyanto; Dian Anggraini; Meliana Fitri; Suhono, Suhono (Yayasan Payungi Smart Madani, 2021)
The purpose of this assistance is to increase the economy of Santri Nurul Anwar through the making of custom paper bags. This research uses Asset Based Community (ABCD) that utilized the potential assets of the community, either social, infrastructure, or individual. Four activities in analyzing the research; Preparing, Participatory Programs, Implementing and Evaluating. Mentoring involves multi-stakeholders and involves students and the Board of Directors of the Nurul Anwar Tejosar Islamic Boarding School. The facilitator also held a workshop which is attended by 50 participants for 2 times, namely the economic strategy workshop in the creative economy sector and also the creativity development of santri in making Paper Bags. The finding from this mentoring show that the students can increase their monthly income independently, apart from engaging in the field of da'wah, the students can develop the field of entrepreneurship that can help with independent finance and also soft skills. Keywords: Entrepreneurship Development, Making Paper Bag, Increasing Economic Santri